Word Of Mouth And Regional Motifs Determine Batik Purchase Decisions: Word Of Mouth Dan Motif Daerah Menentukan Keputusan Pembelian Batik - Intan Nur Hafizah; Sumartik (Proceedings of The ICECRS, 2024)
General Background The traditional textile industry presents significant economic potential but faces intense business competition requiring continuous innovation to sustain market presence. Specific Background Tabinaco Batik, a micro, small, and medium enterprise, develops distinct cultural patterns from Sidoarjo to attract consumers in a highly competitive market. Knowledge Gap Existing literature rarely explores how informal personal recommendations specifically interact with unique regional cultural designs to shape buyer choices in traditional garment enterprises. Aims This research studies the application of informal communication strategies and regional pattern development on consumer purchasing choices. Results Qualitative descriptive analysis involving 41 respondents reveals that peer recommendations and social media reviews heavily shape buying choices. Consumers primarily seek the unique Sidoarjo milkfish-shrimp patterns, supported by product quality, affordable pricing, and responsive service, which lead to high repurchase intentions. Novelty This study integrates cultural pattern specialization with informal communication networks, proving their combined role in sustaining and expanding traditional textile businesses. Implications Traditional enterprises must maintain product uniqueness and leverage digital platforms like Shopee alongside social media to optimize consumer trust and secure long-term transactional commitment. Highlights:  Peer recommendations and social media reviews heavily shape consumer choices. Sidoarjo milkfish-shrimp designs function as the primary attraction for buyers. Affordable pricing and responsive service guarantee high customer retention rates. Keywords: Word Of Mouth, Purchase Decision, Batik Business, Regional Motif, Marketing Strategy